Criminal Responsibility of Child Perpetrators in Crimes of Violence Against Victims in the Form of Imposing Restitution - Hakim, Fathurrohman; Fathurokhman, Ferry; Saputra, Dadang Herli (Fox Justi : Jurnal Ilmu Hukum, 2025)
The absence of additional punishment in the form of restitution imposition on the defendant of the crime of sexual intercourse committed on a child and resulting in pregnancy in the Serang District Court Decision Number: 621/PID.SUS/2019/PN.Srg, certainly creates injustice and will have a direct impact on the child conceived by the victim, because the criminal liability of the defendant O.M.A.J. is no different from the criminal liability of the perpetrator whose actions do not result in pregnancy in the victim's child. The problems in this study are how the imposition of restitution as the responsibility of the perpetrator of sexual intercourse with a child that results in pregnancy, and how criminal law policy regulates the responsibility of the perpetrator of sexual intercourse with a child that results in pregnancy. The method used is normative juridical, using secondary data sources. Data collection techniques by means of documentation studies, and all data collected are analyzed qualitatively. The results of the research show: 1) The imposition of restitution as the responsibility of the perpetrator of sexual intercourse with a child resulting in pregnancy has not been fulfilled in Serang District Court Decision Number: 621/PID.SUS/2019/PN.Srg, where the defendant was sentenced to 10 years imprisonment and a fine of Rp60,000,000, without any additional punishment in the form of imposition of restitution or compensation to the child victim. This is contrary to Article 7 of the Law on Witness and Victim Protection, as well as Article 4 of Supreme Court Regulation Number 1 Year 2022, which states that victims are entitled to restitution; 2) Criminal law policy in regulating the responsibility of perpetrators of sexual intercourse with children resulting in pregnancy has not fulfilled the principle of justice for victims, because the verdict imposed on the defendant in Decision Number: 621/Pid.Sus/2019/PN.Srg did not consider the consequences caused by the defendant's actions which resulted in pregnancy for the victim's child.